Sintering of degradable bone substitutes at room temperature. Issue 15 (1st August 2021) - Lin, Heng-Yi; Huang, Yan-Kai; Hsu, Pei-Yi; Tuan, Wei-Hsing; Naito, Makio
Abstract: The possibility of preparing bone substitutes in clinic is demonstrated in this study. With the addition of a small amount of water, the relative density of the calcium sulfate specimen prepared at room temperature became higher than 92%. This value is close to the density of the specimen prepared through conventional sintering at 1100 °C for 1 h. The biaxial strength of the specimen disc can reach 120 MPa. Densification is assisted by the hydration of calcium sulfate hemihydrate to dihydrate wherein coarse hemihydrate particles transformed to fine dihydrate dendrites. Strength is conferred by the entanglement of dendrites and microstructure refinement. The densified calcium sulfate disc remains degradable; its degradation rate in a phosphate buffer saline solution is 1.6 wt%/day, and the rate remains steady for 28 days.